(untitled) (Global Journal of Science Frontier Research, 2016)
A rapid, sensitive and simple spectrophotometric procedure for the assay of the smaller amounts measures from sodium salicylate at pharmaceutical preparations (topical-solution) was examined. The procedure is focus on a diazotization and reaction coupling between sodium salicylate and diazotized para-amino benzoic acid in alkaline medium for the formation of an intensive bright yellow soluble water colour which was being stable, which gives highly absorption at 452nm. The law of Beer was Introduced on the range of concentration from(2-30) μg.ml -1 of sodium salicylate, the molar absorptivity and the sensitivity of Sandell index were 8.5013×10 3 l mol -1 cm -1 , 0.0188 μg/cm 2 subsequently, The procedure does not need to the control of temperature and the extraction by the solvent. The perfect circumstances for all colour increasing are portrayed and the examined procedure has been very good application on the assay of sodium salicylate at topical-solution preparations. The general excipients materials and additives did not affect the examined procedure.